Ammonia detection in water using balloon-like fiber optic sensor coated with oxazine and PDMS - Abd Rashid, Nurfatihah Che (Elsevier, 2024)
This paper presents the detection of ammonia in water using a balloon-like fiber optic sensor coated with Oxazine 170 perchlorate and polydimethylsiloxane (PDMS). The sensor was prepared by removing a middle portion of a plastic optical fiber cladding using acetone. The uncladded fiber optic sensor was then bent into a balloon-like shape using a 3D printed fiber holder to fix the diameter of the bent structure and a shrink tube to maintain the curvature of the balloon-like structure. A thin layer of Oxazine 170 perchlorate (sensing material) was then deposited on the fiber surface before it was dip coated with PDMS for the protection of the sensing material. Experimental results revealed that the sensor has linear relationship with ammonia concentration ranging from 0 mg/L to 15 mg/L. Moreover, the sensor managed to achieve the sensor sensitivity of 0.006 (mg/L)− 1 , linearity of 0.9154, resolution of 1.6667 mg/L, LOD of 2.9556 mg/L, average stability precision of 99.8 % and RSD of 0.0308 %.